Moon River and me : a memoir - Williams, Andy, 1927-2012. (Waterville, Me. : Thorndike Press, 2009)
Williams shares the memories of his seven remarkable decades in show business.
Keywords: Williams, Andy, -- 1927-2012.; Singers -- United States -- Biography; Large type books